2024
DOI: 10.1140/epjc/s10052-024-12704-x
|View full text |Cite
|
Sign up to set email alerts
|

High-energy QCD dynamics from bottom flavor fragmentation at the Hi-Lumi LHC

Francesco Giovanni Celiberto

Abstract: We study the inclusive production of hadrons with bottom flavor at the LHC and its luminosity upgrade. We describe the collinear fragmentation of singly b-flavored hadrons, B mesons and $$\Lambda _b$$ Λ b baryons, via the determination of fragmentation functions, while for charmed B mesons, $$B_c(^1S_0)$$ B c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 341 publications
0
4
0
Order By: Relevance
“…These findings mark a significant advancement in our understanding of high-energy QCD processes and offer promising prospects for future precision studies in this area. Subsequent analyses on vector quarkonia [253,254,334,335], B c mesons [314,317], and X Qq Q q tetraquarks [318], confirmed that this remarkable feature, known as natural stability of the BFKL resummation [312], comes out as basic property connected to the inclusive emission of any given heavy-flavored particle.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…These findings mark a significant advancement in our understanding of high-energy QCD processes and offer promising prospects for future precision studies in this area. Subsequent analyses on vector quarkonia [253,254,334,335], B c mesons [314,317], and X Qq Q q tetraquarks [318], confirmed that this remarkable feature, known as natural stability of the BFKL resummation [312], comes out as basic property connected to the inclusive emission of any given heavy-flavored particle.…”
Section: Introductionmentioning
confidence: 94%
“…Version v0.4.7 [253] introduced quarkonium-sensitive reactions from NRQCD leadingtwist fragmentation. Novel features in v0.5.0 [254] and v0.5.1 [317] encompass an enhanced system for MHOU-related studies, an expanded list of observables with a focus on singly-and doubly-differential transverse-momentum production rates [276,289,317], and support for matching procedures with collinear factorization [324][325][326][327]329]. The most significant update of v0.5.2 is symJETHAD, a MATHEMATICA plugin devoted to symbolical calculations for high-energy QCD and the proton structure.…”
Section: Heavy Hadrons With Jethadmentioning
confidence: 99%
See 2 more Smart Citations